Tecnoplastia. Note sulla poiesi macchinica - Tenti, Gregorio (Philosophy Kitchen - Rivista di filosofia contemporanea, 2023)
This article examines a chapter in the history of machines, namely the study of chaotic behaviours through machinic simulations, in order to draw theoretical conclusions on artificial creativity and the nature of computational processes. The first paragraph traces the early history of physics of chaos in its epistemological implications. The second paragraph investigates how machines are able to simulate chaotic behaviours by increase of internal entropy, and thus to make themselves sensitive to the heterogeneous texture of nature itself. Particular attention will be devoted to the so-called principle of “order from noise”, elaborated within the second-order cybernetics. This will lead to consider machines as material fields established around the acts of execution of a program, which thus become acts of materialization and interpretation thereof. In conclusion, the terms «technoplasty» and «machinic poietics» will be proposed to conceptualize a wider shift towards nonrepresentational technologies.